Having the Lower Hand—Investigating Interaction in the Life Course Narratives of Immigrant Women Exposed to Partner Abuse - Liversage, Anika (Journal of interpersonal violence, 2022)
Research has documented the considerable hardships immigrant women often face if they want to leave abusive relationships, but the cumulative impacts of such experiences have received insufficient scholarly attention. In response, this study investigates women?s difficulties leaving abusive relationships based on life story interviews with 35 immigrant women who experienced partner abuse. Almost all the women originated from ?patriarchal belt? countries in, for example, the Middle East and all arrived in Denmark as adults. Using a model of gendered geographies of power, this study examines key interview passages in which the women use dramatized speech to tell about their younger selves? interactions with significant others. These dramatized episodes of interactions emerge as crucial for the interviewees to communicate why they remained in abusive relationships for years and how most finally managed to leave their husbands. The narrated episodes reveal how the women?s frequent lack of success in various interactional situations can be attributed to women ?having the lower hand??holding disadvantaged positions in the familial, social, and national hierarchies of power. These hierarchies reinforce each other, for example, when insecure residency status limits immigrant women?s options to solicit help from Danish society. The analysis demonstrates that?in contrast to the stereotype of the abused immigrant woman as a passive victim?micro- and macro-level processes may work together to undermine immigrant women?s possibilities to act independently at important junctures in their lives. The results also stress the importance that frontline workers have sufficient understanding of immigrant women?s predicament and the ability to extend qualified and timely support. Such support can be crucial for abused immigrant women to become able to move away from their violent home environments.